1992
DOI: 10.1037/0033-2909.112.2.284
|View full text |Cite
|
Sign up to set email alerts
|

Emotional stress and eyewitness memory: A critical review.

Abstract: The eyewitness literature often claims that emotional stress leads to an impairment in memory and, hence, that details of unpleasant emotional events are remembered less accurately than details of neutral or everyday events. A common assumption behind this view is that a decrease in available processing capacity occurs at states of high emotional arousal, which, therefore, leads to less efficient memory processing. The research reviewed here shows that this belief is overly simplistic. Current studies demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

67
737
7
37

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 922 publications
(859 citation statements)
references
References 200 publications
67
737
7
37
Order By: Relevance
“…Proxy reports are frequently used in palliative care research due to the difficulties encountered in research engaging people with a life-limiting illness [2,4,11,31,33]. Studies have examined the accuracy of retrospective reports by proxies, comparing reports of patients prior to death with those of their relatives after death [4,10,22,27,31,33].…”
Section: Limitations-methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proxy reports are frequently used in palliative care research due to the difficulties encountered in research engaging people with a life-limiting illness [2,4,11,31,33]. Studies have examined the accuracy of retrospective reports by proxies, comparing reports of patients prior to death with those of their relatives after death [4,10,22,27,31,33].…”
Section: Limitations-methodsmentioning
confidence: 99%
“…In a population survey of this nature, deaths theoretically should be evenly distributed in each of the years across the 5-year period. This apparent anomaly may be due to recall error given that life-changing or highly emotional life events may feel more recent than they actually were [2,11].…”
Section: Limitations-samplementioning
confidence: 99%
“…In particular, studies have demonstrated that emotional arousal can impede perceptual memory (Richards andGross, 1999, 2000;Richards, 2004) and increase memories for emotional states (Richards et al, 2003). One explanation that has been proposed for this efffect is that expressive suppression and memory retention compete for cognitive resources, a notion that corresponds with a general resource depletion model of executive function in which attention, working memory, and voluntary thought and behaviour utilise the same frontal regions in the human brain (Yerkes and Dodson, 1908;Ellis and Ashbrook, 1989;Christianson, 1992;Wegner et al, 1993;Engle et al, 1995;Kirchbaum et al, 1996;Baumeister et al, 1998;Macrae et al, 1998;Schjoedt et al, 2011Schjoedt et al, , 2013. This efffect may be especially relevant in highly arousing social events where cultural norms impose strong expressive suppression on participants.…”
Section: Discussionmentioning
confidence: 99%
“…the kinds of information and details that most resist distortion (e.g., Christianson & Loftus, 1990;Heuer & Reisberg, 1992), and how valenced stimuli, mood states, or levels of arousal modulate these effects (e.g., Bradley, Greenwald, Petry,& Lang, 1992;Bower & Forgas, in press;Christianson, 1992). …”
mentioning
confidence: 99%